Newly discovered species of cheilostomatid Bryozoa from the Miocene of western Kachchh, Gujarat, India - Sonar, Mohan A.; Pawar, Ravi V.; Wayal, Dnyaneshwar V. (European Journal of Taxonomy, 2022)
Cheilostomatid bryozoans are present in large quantities in Miocene sediments of western Kachchh. A detailed investigation, as presented here, has yielded 11 species. Among them, two species – Canda ukirensis sp. nov. and Antropora ramaniaensis sp. nov. – are new to science. Five species had already been reported from the same region, while a genus and the remaining three species are left in open nomenclature pending an exhaustive study using better preserved material.